Pemberdayaan Masyarakat Gampong Dilib Lamteungoh, Kecamatan Sukamakmur, Kabupaten Aceh Besar dalam Mewujudkan Lingkungan Hijau Melalui Pelatihan Ecoenzim - Sy., Yuliana; Mulana, Farid; Sayuthi, Muhammad; Rahman, Aulia; Nasution, Fahrizal; Ambarita, Aulia Chintia; Sofyana, Sofyana (Universitas Syiah Kuala, 2025)
This community service program was conducted in Dilib Lamteungoh Village, Sukamakmur Sub-District, Aceh Besar Regency, with the objective of improving the communitys knowledge and skills in managing household organic waste through eco-enzyme production training. The activity involved 22 participants, primarily farmers and housewives. The implementation methods included lectures, hands-on demonstrations, and pre-test and post-test evaluations to assess participants knowledge improvement. The eco-enzyme formulation used a ratio of palm sugar : organic waste : water = 1 : 3 : 10, followed by a three-month fermentation process in shaded, tightly closed containers. The results indicated a significant increase in participants understanding and active involvement. All participants (100%) were able to correctly describe the process of eco-enzyme production, and 86.4% expressed their intention to continue making eco-enzymes independently at home. Moreover, participants gained awareness of the eco-enzymes multifunctional benefits, including its use as liquid organic fertilizer, natural household cleaner, and organic waste decomposer. Overall, the program successfully fostered environmental awareness and community participation, promoting sustainable waste management practices and encouraging the realization of an environmentally conscious and self-reliant rural community.